NF-κB transcription factor role in consolidation and reconsolidation of persistent memories - de la Fuente, Verónica; Federman, Noel; Zalcman, Gisela; Salles, Angeles; Freudenthal, Ramiro; Romano, Arturo G. (Frontiers in Molecular Neuroscience, 2015)
Transcriptional regulation is an important molecular process required for long-term neural plasticity and long-term memory formation. Thus, one main interest in molecular neuroscience in the last decades has been the identification of transcription factors that are involved in memory processes. Among them, the NF-κB family of transcription factors has gained interest due to a significant body of evidence that supports a key role of these proteins in synaptic plasticity and memory. In recent years, the interest was particularly reinforced because NF-κB was characterized as an important regulator of synaptogenesis. This function may be explained by its participation in synapse to nucleus communication, as well as a possible local role at the synapse. This review provides an overview of experimental work obtained in the last years, showing the essential role of this transcription factor in memory processes in different learning tasks in mammals. We focus the review on the consolidation and reconsolidation memory phases as well as on the regulation of immediate-early and late genes by epigenetic mechanisms that determine enduring forms of memories.